Die Gesellschaft verändern: Zur Strategieentwicklung in Basisgruppen der deutschen Umweltbewegung - Bosse, Jana (transcript, 2019)
Strategies in environmental protection groups are not dictated by grievances, but are the result of an exciting social interpretation and negotiation process.